Tackling maternal mortality in Pakistan: A perspective and call for systemic improvements - Singh, Ajeet; Raza, Alishba (Journal of the Pakistan Medical Association, 2023)
Dear Madam, Pregnancy should be a time of immense hope and a positive experience for all women. This period necessitates significant management and care, as the woman’s body undergoes numerous physiological and psychological adaptations. Thus, establishing an effective management system and a proficient maternal healthcare service is of utmost importance for the mother and the children. However, in developing countries like Pakistan, it is still a shockingly scary experience for millions of pregnant women who lack access to high-quality healthcare systems. For many females, the miracle of childbirth is marred by the tragedy of maternal death. Maternal death is defined as the death of a woman while pregnant or within 42 days of termination of the pregnancy, irrespective of the duration and site of the pregnancy, from any cause related to or aggravated by the pregnancy or its management but not from accidental or incidental causes [1]. Additionally, Pakistan has been ranked as one of the top ten countries expected to contribute 60% of all maternal deaths worldwide [2]. It continues to have the highest maternal deaths in Southeast Asia [3]. Despite Pakistan being officially categorized as a country with high maternal mortality rates, the actual number of cases could be even higher due to under-registration of vital events, particularly in the rural parts of the country [4]. Nevertheless, based on interview survey methods, the maternal mortality ratio in Pakistan is estimated to have declined from 430/10^5 live births in 1990 to 180/10^5 in 2015 [2]. However, the recent report, "Trends in Maternal Mortality", released by WHO, UNICEF, UNFPA, the world bank, and UN Population Division, reveals alarming setbacks for women's health over recent years, as maternal deaths either increased or remained stalled in nearly all regions of the world after 2015 [5]. The report statistics indicate a public health emergency that a woman dies every two minutes due to complications associated with pregnancy or childbirth. It emphasizes that the world must significantly accelerate progress in reducing maternal deathsor risk the lives of over one million more women by 2030 [5]. While the entire global community contends with the maternal mortality, Pakistan shoulders a disproportionate share of its consequences [2]. ---Continue